Pengaruh Supervisor Relationship dan Sifat Machiavellian terhadap Dysfunctional Audit Behavior - Desi Afrizalita; Charoline Cheisviyanny (Universitas Negeri Padang, 2023)
The purpose of this study is analyze the effect of supervisor relationship and Machiavellianism on dysfunctional audit behavior. The effect of supervisor relationship and Machiavellianism on DAB tested by using a quasi experimental with 2x2 factorial design. The ANOVA measurement are used to test hypothesis in this study. The conclusions that can be drawn in this study are subjects in positive relationship with their seniors tended to do DAB. And also in this study it can be concluded that high Machiavellian and low Machiavellian have no effect on DAB. There is an interaction effect between supervisor relationship and Machiavellian that affect to DAB.